Potential Sources of Particulate Iron in Surface and Deep Waters of the Terra Nova Bay (Ross Sea, Antarctica) - Paola Rivaro; Francisco Ardini; Davide Vivado; Roberto Cabella; Pasquale Castagno; Olga Mangoni; Pierpaolo Falco (Water, 2020)
The distribution of particulate Fe (pFe), suspended particulate matter (SPM), and other particulate trace metals were investigated in Terra Nova Bay as part of CDW Effects on glaciaL mElting and on Bulk of Fe in the Western Ross sea (CELEBeR) and Plankton biodiversity and functioning of the Ross Sea ecosystems in a changing Southern Ocean (P-ROSE) projects. Variable concentrations of SPM (0.09–97 mg L−1), pFe (0.51–8.70 nM) and other trace metals were found in the Antarctic Surface waters (AASW) layer, where the addition of meltwater contributed to the pool with both lithogenic and biogenic forms. The deeper layer of the water column was occupied by High Salinity Shelf Water (HSSW) and Terra Nova Bay Ice Shelf Water (TISW) encompassing glacial water as confirmed by the lightest δ18O measured values. The concentration of pFe in TISW (11.7 ± 9.2 nM) was higher than in HSSW samples (5.55 ± 4.43 nM), suggesting that the drainage of material released from glaciers surrounding the area is relevant in terms of pFe contribution. Particulate Fe/Al and Mn/Al ratios were substantially in excess compared with the mean crustal ratios. Microscopic analyses confirmed that more labile Fe oxyhydroxides and authigenic MnO2 phases were present together with biogenic sinking material. Future expected increasing melt rates of these glaciers enlarge Fe input, thus having a greater role in supplying iron and counteracting the reductions in sea ice cover around Terra Nova Bay.